2012
DOI: 10.1128/jvi.01705-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analyses of Zta Binding to the Epstein-Barr Virus Genome Reveals Interactions in both Early and Late Lytic Cycles and an Epigenetic Switch Leading to an Altered Binding Profile

Abstract: cThe Epstein-Barr virus (EBV) genome sustains substantial epigenetic modification involving chromatin remodelling and DNA methylation during lytic replication. Zta (ZEBRA, BZLF1), a key regulator of the EBV lytic cycle, is a transcription and replication factor, binding to Zta response elements (ZREs) in target promoters and EBV lytic origins of replication. In vitro, Zta binding is modulated by DNA methylation; a subset of CpG-containing Zta binding sites (CpG ZREs) is bound only in a DNA methylation-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 43 publications
0
40
1
Order By: Relevance
“…In particular, ICP4, which has been shown to be important for the recruitment of the cellular TBP to late gene promoters (36), contains a unique uracil-DNA glycosylase-like domain potentially involved in this process (37). Until now, a direct implication of the CMV or EBV immediate early factors in the regulation of late viral genes has not been described, except for particular genes like that encoding the EBV BLLF1 protein (gp350), whose expression is induced by Rta (6,38). It is thus tempting to speculate that the EBV BcRF1 protein and its analogs in beta-and gammaherpesviruses play the role of cellular TBP (18).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ICP4, which has been shown to be important for the recruitment of the cellular TBP to late gene promoters (36), contains a unique uracil-DNA glycosylase-like domain potentially involved in this process (37). Until now, a direct implication of the CMV or EBV immediate early factors in the regulation of late viral genes has not been described, except for particular genes like that encoding the EBV BLLF1 protein (gp350), whose expression is induced by Rta (6,38). It is thus tempting to speculate that the EBV BcRF1 protein and its analogs in beta-and gammaherpesviruses play the role of cellular TBP (18).…”
Section: Discussionmentioning
confidence: 99%
“…The master regulator of the latent-lytic cycle switch, BZLF1, binds directly to Zta response elements throughout the viral genome and activates both early and late lytic cycle genes (45). BZLF1 does not rely on DNA binding proteins, such as RBP-JÎș, to activate the promoters of the lytic cycle genes, so it is not regulated by Notch at this level.…”
Section: Discussionmentioning
confidence: 99%
“…These promoters contain CpG-containing Zta response elements (CpG-ZREs). Highly methylated ZREs were associated with high Zta occupancies (73). Our data suggest that Rta expression provides methylation marks in the viral promoters for Zta binding during latent-lytic cycle transition.…”
Section: Discussionmentioning
confidence: 63%
“…It has been demonstrated that a methylated EBV genome is essential for viral lytic reproduction (51,53,72), as the immediate-early protein Zta preferentially binds to methylated viral promoters (54,(73)(74)(75). In 293T cells stably infected with an EBV genome, high occupancies of Zta were observed in methylated promoters of BALF2, BMRF1, Rta, and BHLF1, whereas these bindings were disrupted once the EBV genome is hypomethylated (54).…”
Section: Discussionmentioning
confidence: 99%